The association between mental health literacy and positive coping strategies in junior high school students: evidence from a moderated mediation model - Chen Chen; Lishuang Zhu; Yang Zhao; Xiaoming Liu (Frontiers in Psychology, 2026)
Purpose This study explores how mental health literacy relates to coping behavior in junior high school students, focusing on mediation of the association by self-efficacy and moderation by perceived teacher support. Methods Information was collected from 631 junior high school students using various questionnaires, including the Adolescent Coping Strategies Scale, the Chinese version of the Adolescent Mental Health Literacy Scale, the General Self-Efficacy Scale, and the Student Perceived Teacher Support Behavior Scale. Results All primary variables, including mental health literacy, self-efficacy, perceived teacher support, and positive coping strategies, were significantly intercorrelated. Self-efficacy was found to mediate the association between mental health literacy and positive coping strategies. Additionally, perceived teacher support moderated both the pathway from mental health literacy to self-efficacy and the subsequent development of positive coping strategies. Conclusion Mental health literacy positively predicts the development of positive coping strategies strategies in junior high school students. Self-efficacy partially explains this relationship, indicating that mental health literacy influences coping both directly and indirectly by strengthening students' confidence in their abilities. Perceived teacher support exhibits a moderating effect that enhances the positive link between mental health literacy and self-efficacy, while attenuating the link between self-efficacy and positive coping strategies. The findings revealed the complex mediating and moderating mechanisms between mental health literacy and positive coping styles, and have profound implications for schools in enhancing positive coping styles among junior high school students.